Effects of zinc and boron on yield, nodulation and nutrient contents of fieldpea in terrace soils (Bangladesh Journal of Agricultural Research, 2018)
An experiment was conducted for two consecutive years (2014-15 and 2015-16) in the field of Pulses Research Sub-Station, BARI, Gazipur during rabi (winter) season to evaluate the effect of zinc (Zn) and boron (B) application on the yield, nodulation and nutrient content of fieldpea (Pisum sativum L.). There were 16 treatment combinations comprising four levels each of zinc (0, 1, 2 and 3 kg ha-1) and boron (0, 1, 1.5 and 2 kg ha-1) along with a blanket dose of N12 P18 K30 S10 kg ha-1 over the treatments. The experiment was laid out in a split-plot design with three replications. Zinc (Zn) as ZnSO4.7H2O and boron (B) as H3BO3 were applied to the crop (cv. BARI Fieldpea-1). Results showed that the combination of Zn3B1.5 kg ha-1 produced the highest seed yield (1582 kg ha-1) in the 1st year and the Zn3B2 kg ha-1 gave the highest yield (1702 kg ha-1) in the 2nd year.The lowest seed yield was found in the control (Zn0B0). The Zn3B2 demonstrated the highest nodulation and nutrient and protein contents. The results suggest that the application of Zn3B2 kg ha-1 along with N12 P18 K30 S10 kg ha-1 can support the higher yield of fieldpea in terrace soils of Bangladesh.Bangladesh J. Agril. Res. 43(3): 441-451, September 2018